2020
DOI: 10.1080/19942060.2019.1704886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moving train on the aerodynamic performances of train-bridge system with a crosswind

Abstract: Some aerodynamic results about the effect of moving train on the aerodynamics of train-bridge system in crosswinds are introduced using a computational fluid dynamics (CFD) method. In the simulation, a new overset mesh approach is applied to present the motion of trains, and the results are compared with that of the scaled wind tunnel experiment to validate the accuracy of the mesh and algorithm. Besides, the aerodynamic characteristics associated with the train and bridge are discussed for a range of resultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…In the numerical simulation, two trains passing each other and the relative motion between the train and other railway infrastructures (e.g., tunnels, wind barriers, and bridges) can be analysed using the dynamic mesh method [33,34], sliding mesh method [1,[35][36][37], and overset mesh method [12,21,38,39]. Nevertheless, the dynamic mesh method needs to regenerate the mesh at each time step, which may increase the calculation time.…”
Section: Mesh Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the numerical simulation, two trains passing each other and the relative motion between the train and other railway infrastructures (e.g., tunnels, wind barriers, and bridges) can be analysed using the dynamic mesh method [33,34], sliding mesh method [1,[35][36][37], and overset mesh method [12,21,38,39]. Nevertheless, the dynamic mesh method needs to regenerate the mesh at each time step, which may increase the calculation time.…”
Section: Mesh Generationmentioning
confidence: 99%
“…However, the number of grids required for the sliding mesh method is greater than that required for the overset mesh method with the same grid refinement method. Furthermore, the overset mesh method is suitable for complex and irregular moving models owing to its decomposition and overlapping techniques [39]. Consequently, the overset mesh method was applied in this study.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Unsteady incompressible N-S equations are used to solve the flow field for the cases with a train running on the bridge and pass by the wind barrier. A Shear Stress Transport (SST) turbulence model is widely used in numerical simulation of the flow around the train (Liang et al, 2020;Yao et al, 2020), which is designed to deal with adverse pressure gradients and separated flows (Menter et al, 2003). The SST k-ω turbulence model is used as the turbulence closure for the RANS equations listed below:…”
Section: Numerical Schemesmentioning
confidence: 99%
“…wind/sound barriers. Recently, some moving model tests have been carried out to highlight the unsteady characteristics of the aerodynamic forces caused by a running train under crosswind (Wang et al, 2018;Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have suggested that to cope with severe weather, which includes wind and sandstorm, to ensure the safe operation of trains in strong winds, and to improve the aerodynamic performances of trains, windbreaks should be built along the railways (Baker, 1986;Barcala & Meseguer, 2007;Bocciolone et al, 2008;Chu et al, 2013;He et al, 2014;T. Liu et al, 2018;Niu et al, 2018;Yao et al, 2020). Xinjiang has a special geographical location and a complex CONTACT Tanghong Liu lth@csu.edu.cn; Yutao Xia xytcsu@csu.edu.cn climatic environment.…”
Section: Introductionmentioning
confidence: 99%